Genetic and epigenetic mechanisms of regulation of human papillomavirus - S. V. Vinokurova (Успехи молекулярной онкологии)
Infections with high-risk human papillomaviruses (HPV) are the etiological factor of certain types of human cancers in anogenital tract and head and neck cancers. Extensive epidemiological studies demonstrated the association of persistent high-risk HPV infection and the later development of cervical and other cancers. Experimental data using cell lines models and cervical cancers demonstrate that in more than 99 % of clinical samples the viral E6 and E7 genes are retained and expressed. These genes can transform human cells and inhibition of their expression in cancer cells results in loss of neoplastic growth properties. Molecular mechanisms of immortalization and transformation by E6 and E7 have extensively been investigated. However, the mechanism of E6 and E7 deregulation that triggers the shift from permissive infection to neoplastic transforming infection is still unclear. This review describes the current knowledge about the viral life cycle and discusses the molecular mechanisms that potentially allow the virus to escape its normal control and may trigger neoplastic progression. The molecular clarification of these events required for transformation of HPV-infected cells into cancer will provide a basis for conceptually novel diagnostic and therapeutic strategies and approaches.